Artificial intelligence: a review of the scientific literature in Scopus - Collazos Alarcon, Mercedes Alejandrina (2023)
Artificial intelligence (AI) has revolutionized conventional work methods in all areas of knowledge. The aim of this study is to analyze the current state of research in this field. To this end, a systematic review was carried out with a bibliometric approach that included analysis of the distribution of scientific production by year, the most relevant sources, Bradford's Law to identify the main sources, the most prominent authors, Lotka's Law to analyze the productivity of authors and the author's "h" index. Through the review of the scientific literature available in the Scopus database, 609 relevant results were identified, of which 414 were articles in Spanish. A total of 205 articles were selected as the final publication of the study and 113 of them were open access. The empirical studies demonstrate that AI presents both opportunities and ethical and social challenges, especially in areas such as health, communication, law and artistic practices. In healthcare, AI can improve patients' quality of life. In journalism, AI streamlines the production of objective news and helps reduce misinformation, although it also poses ethical and professional challenges. In the field of law, AI offers opportunities to improve efficiency in judicial decision-making and legal work, but it also brings ethical and legal considerations. It is therefore essential to strike a balance between harnessing the benefits of AI and protecting rights, privacy and ethics in each of these fields, in order to maximize its potential for the benefit of society.